Weakening Tradition: The Shifting in Same-Clan Marriage Prohibition in Mandailing Batak - Ahmad Mukri Aji; Mara Sutan Rambe; Nur Rohim Yunus; Rulia Feriera (AHKAM : Jurnal Ilmu Syariah, 2021)
Same-clan marriage is prohibited among the Mandailing Batak society. The practice is considered to harm partuturon (designation within the family relationship). However, people have started to violate this prohibition. Sanctions for the violators have no longer been imposed. This indicates the weakening of the customary law in society. This is a legal anthropological inquiry involving observations and interviews with the customary leaders of the Mandailing Batak Society and those who practice the same-clan marriage. This research finds that factors influencing the changes in the same-clan marriage include Islamic teachings, modernity, improvement in education, and people's mobility.   Abstrak: Perkawinan sesama marga dilarang di kalangan masyarakat Batak Mandailing. Praktik tersebut dianggap merugikan partuturon (sebutan dalam hubungan keluarga). Namun, larangan tersebut sudah mulai dilanggar oleh masyarakat. Sanksi bagi pelanggar sudah tidak berlaku lagi. Hal ini menunjukkan melemahnya hukum adat dalam masyarakat. Penelitian antropologi hukum ini menggunakan observasi dan interview kepada para pemimpin adat Masyarakat Batak Mandailing dan mereka yang melakukan perkawinan sesama marga. Penelitian ini menemukan bahwa faktor-faktor seperti modernitas, peningkatan pendidikan, mobilitas, dan ajaran Islam mempengaruhi perubahan perkawinan sesama marga.